Secular trends of the prevalence of emaciation, overweight, and obesity among school-aged children in Yunnan province, 1985–2019: A serial cross-sectional surveillance study in China - Yang, Yunjuan; Dai, Jing; Huang, Songquan; Li, Tunan; Song, Zhizhong; Zha, Shun; Ma, Chengpeng; Chang, Litao; Zhang, Song; Liu, Hong; Wei, Diexin; Yang, Fan; et al. (Frontiers in Nutrition, 2022)
Objectives To understand the trends of nutrition in children and adolescents which may further help to prevent and control chronic diseases in younger ages. Methods The CNSSCH in Yunnan is a survey of growth conditions, physical fitness and health status in Yunnan students that uses a series of complex multistage stratified sampling of 7 prefectures consisting of 16 counties. The sampling schools kept consistent in 35 years. We used data in 1985, 1991, 2000, 2005, 2010, 2014 and 2019 CNSSCH of Yunnan. A participant was considered nutrition (emaciation, overweight or obesity) according to the body mass index (BMI) criteria from the National Working Group for Obesity in China (WGOC-BMI criteria). 129,520 participants were randomly selected among 7-18 aged students from 1985 to 2019. Account of it, in 1985 (n=14,683), 1991 (n=4,894), 1995 (n=6,673), 2000 (n=9,751), 2005 (n=23,461), 2010 (n=22,889), 2014 (n=23,003) and 2019 (24,166). Results Since 1985, emaciation trend of 35 years was a decreasing trend. Regardless of gender, area and age, the prevalence of obesity and overweight was increased. The average annual growth rate of overweight and obesity in rural areas and boys was quicker than that of the urban and girls. Areas and gender disparity in children’s emaciation, overweight and obesity were common phenomenon in Yunnan. Conclusions Children’s nutrition in Yunnan faced the triple burden of emaciation, overweight and obesity. We should take comprehensive policies and effective intervention measures to decrease rate of school-aged children nutrition problem.